Impedance Planimetry for Crohn's Disease Anastomotic Stricture Characterization: A Predictor of Treatment Response?. Issue 1 (17th January 2022) - Ismail, Mohamed Saleh; Akshintala, Venkata S.; Kumbhari, Vivek; Selaru, Florin M.
ABSTRACT: Intestinal strictures affect one-third of patients with Crohn's disease (CD) within 10 years of disease onset. Quantification of fibrosis and/or inflammation within the stricture may help in choosing the appropriate treatment. Current endoscopic imaging modalities could benefit from the transmural characterization of tissue modeling from fibrosis. We report the application of EndoFLIP during balloon dilation and stricturotomy of CD-related ileocolonic anastomotic stricture. A low EndoFLIP distensibility was noted which improved after endotherapy. This proof-of-concept application supports the use of EndoFLIP to characterize CD anastomotic stricture and real-time assessment of response to endotherapy.